Protective Effects of Pinocembrin on Organic Anion Transporter 3 Protein Function in Kidney of Gentamicin-treated Rats - Sasivimon Promsan (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Gentamicin is one of antibiotics, which is in an aminoglycoside group and most commonly used to treat many types of bacterial infections, particularly those caused by gram-negative organisms. However, its clinical use is partially limited due to its nephrotoxicity. Neprotoxicity is a serious side effect of gentamicin and is related to the increased reactive oxygen species (ROS) in the kidney. Pinocembrin is one of the flavonoids at the highest concentration in propolis and the rhizomes of fingerroot (Boesenbergia pandurata). It has several biological actions including antimicrobial, anti-inflammatory and antioxidant effects. This present study was designed to investigate a possible potential protective role of pinocembrin against gentamicin-induced nephrotoxicity. Sprague-Dawley rats (240-250 g) were randomly divided into four groups; Control (rats were injected intraperitoneally (i.p.) with tween-80 for 10 days); Pinocembrin (pinocembrin at the dose of 50 mg/kg/day dissolved in tween-80 was injected i.p. for 10 days); Gentamicin-treated rats (tween-80 and gentamicin (100 mg/kg/day) were injected i.p.) and Gentamicin+pinocembrin (pinocembrin was administered i.p. 30 minutes before gentamicin treatment for 10 days) (each group, n = 6). At the end of the experiment, body weight (BW), ratio of kidney weight to body weight (KW/BW ratio), serum blood urea nitrogen (BUN), serum creatinine (Cr), urine creatinine and glomerular filtration rate (GFR) were determined. Malondialdehyde (MDA) and superoxide dismutase (SOD) in renal cortical tissues were used to evaluate oxidative stress condition. [3H]Estrone sulfate (ES) uptake into renal cortical slices was examined to reflect the renal Oat3 function. Histological changes of the kidneys were examined by hematoxylin and eosin (H&E) staining. The expressions of renal Oat3, PKCα, Nrf2, HO-1 and NQO1 were determined using western blotting. The present study showed that serum BUN and creatinine were significantly increased while urine creatinine and GFR were significantly reduced in the gentamicin-treated rats. Moreover, the increase in renal cortical MDA level was demonstrated in the gentamicin group compared with the control. Hematoxylin and eosin (H&E) staining showed normal glomerular structure but tubular dilatation was occurred within the renal proximal tubule cells in the gentamicin-treated rats. The function of Oat3 which represented by [3H]ES uptake into renal cortical slices was significantly decreased in the gentamicin-treated rats which related to the reduced membrane expression of renal Oat3 expression in the renal cortex. Furthermore, the expressions of PKCα, Nrf2, HO-1 and NQO1 were significantly increased in gentamicin-treated rats. Pinocembrin pretreatment caused a significant increased in renal function as well as the up-regulation of the renal Oat3 function as indicated by the increase in [3H]ES uptake. Pinocembrin also improved oxidative stress condition as shown by the attenuating renal MDA level in gentamicin-treated rats. These results indicated that pinocembrin has the renoprotective effects against acute kidney injury induced by gentamicin which might be due to, in part, the decreasing overoxidation of the kidney leading to the increase in renal Oat3 expression and function.